Pharmacognostic specifications and the antioxidant activity of Curcuma comosa Roxb. crude drugs - Hartanti, Dwi; Kitphati, Worawan; Peungvicha, Penchom; Chatsumpun, Nutputsorn (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2023)
Curcuma comosa Roxb. is popularly used to treat gynecological problems but has no official monograph in the Thai Herbal Pharmacopeia (THP). This study characterized the selected pharmacognostic and physicochemical specifications and antioxidant potentials of C. comosa crude drugs. The pharmacognostic and physicochemical properties of two kinds of crude drugs were characterized according to the WHO quality control methods for herbal materials. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity, ferric reducing antioxidant power (FRAP), and total phenolic content (TPC) were evaluated as per the standard method. The microscopic observation showed relatively large-sized starch granules, cortical parenchyma, vessel, and sclerenchyma fibre. The thin-layer chromatography (TLC) profile demonstrated distinct separation with two major spots. The physicochemical evaluations specified as follow: moisture (8.87±1.37%), total ash (2.35±0.12%), acid-insoluble ash (0.80±0.08%), volatile oil (1.01±0.03%), water-soluble extractable (16.01±0.95%), and ethanol-soluble extractable (17.74±1.56%). The DPPH scavenging activity, FRAP, and TPC of the crude drugs were 765.56±80.50 mM Trolox equivalent (TE)/g dry weight (DW), 505.42±22.44 mM TE/g DW, and 46.09±2.27 mg Gallic acid equivalent (GAE)/g DW. This study specified quality parameters of C. comosa crude drugs that might serve as the reference for the quality control purpose.